Michael Howard and Clausewitz. Issue 1 (2nd January 2022) - Strachan, Hew
ABSTRACT: The English translation of Carl von Clausewitz's On War by Michael Howard and Peter Paret has had a major impact on how Clausewitz is read today, especially in the United States and Britain. Howard in particular was determined to make Clausewitz doubly relevant – as one soldier speaking to other soldiers and as an author whose views on war had continuing purchase. However, the result is a text which, in reflecting the issues of its day, is not fully reflective of what Clausewitz himself said and has itself become dated.